A Wrong Turn in History: Re-understanding the Exclusionary Rule Against Prior Negotiations in Contractual Interpretation - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2014)
A reason justifying the exclusionary rule against prior negotiations in the interpretation of contracts is its longevity. Yet, the authorities commonly cited in support of the exclusionary rule are mostly traceable to Lord Wilberforce’s speech in the relatively recent case of Prenn v Simmonds. This article suggests that the law took a wrong turn in that case and caused later courts to support the exclusionary rule by recourse to policy-oriented justifications, instead of principle-based ones. The emphasis on policy-oriented justifications, and the recantation of Prenn v Simmonds as reason enough for the exclusionary rule, support an independent rule against prior negotiations that was never meant to be.The consequence is the judicial (and academic) acknowledgement of the exclusionary rule’s uncertain boundaries, and the simultaneous maintenance of its legitimacy.